Anti-allergic potentials of Ceriops decandra leaves in TDI-induced allergic mice: Comprehensive in-vivo and in-silico studies - Aishwarja Dey; Subarna Rani; Rabindra Nath Acharyya; Apurba Kumar Barman; Khondoker Shahin Ahmed; Nripendra Nath Biswas; Shrabanti Dev; Asish Kumar Das (Phytomedicine Plus)
Background: Ceriops decandra is a mangrove plant, locally known as “Goran”. This plant has been traditionally used to treat hepatitis, liver disorders, ulcers, diarrhea, gastrointestinal disorders, hemorrhage, pain, inflammation etc. Here we investigated the safety and anti-allergic potential of C. decandra leaves. Method: The toxicity was screened by mortality rate, and behavioral changes in mice. Anti-allergic activity test was conducted on TDI induced allergy model mice by assessing the common allergic symptoms such as sneezing, scratching, nasal score as well as total and differential WBC counts. HPLC-DAD analysis was used to determine the polyphenolic compounds in crude extract and performed in-silico molecular docking against four potential receptor molecules (Histamine H1, Histidine decarboxylate, Interleukin- 4 and 5). Results: The toxicity study of the extract on mice showed the innocuous nature of the plant even at the highest dose of 3000 mg/kg. In the anti-allergic assay, the leaf extract significantly (p < 0.05) decreased the allergic symptoms along with the WBC counts in blood in a dose-dependent manner. The HPLC profile revealed the presence of six phenolic compounds (Catechin hydrate, Caffeic acid, Vanillic acid, Syringic acid, Rutin hydrate, p-coumarin). Among those Rutin hydrate, exhibited the best docking scores at all the targeted protein molecules and the highest binding affinity was (-9.8 kcal/mol) against Interleukin-5. Conclusion: C. decandra is safe and rich in several polyphenolic compounds which are effective against allergic syndromes which could be an effective option for the management of allergic symptoms, although clinical studies are required to establish the herbal formulation.